Antioxidant and Apoptotic Effect of Edaravone on Cisplatin-Induced Brain Injury in Rats - Ozlem Kara; Asuman Kilitci (Acta Neurologica Taiwanica)
Purpose: This study aims to investigate the effect of edaravone in preventing cisplatin-induced brain damage. Methods: Forty female Wistar albino rats were included in the study. 4 groups were created. In group 1 (control group) (n=10), neither any drugs were given nor anything was performed. Group 2 (cisplatin group) (n=10), single dose 7.5 mg/kg cisplatin was given. In group 3 (edaravone group) (n=10), single dose 1 mg/kg edaravone was administered. Group 4 (cisplatin+ edaravone group) (n=10), single dose 7.5 mg/kg cisplatin and 1 mg/kg edaravone were given. Brain tissue was removed in all rats after 3 days. Blood samples taken from heart tissue were examined for malondialdehyde (MDA) and nitric oxide (NO) levels. Brain tissue was evaluated for damage with p53, GFAP and Ki 67. Results: Edaravone reduced cisplatin-induced brain damage. MDA and NO levels in the cisplatin group were significantly higher than the other groups (p< 0.05). Likewise, tissue damage in the cisplatin group was significantly higher than in the other groups (p< 0.05). The immunohistochemical staining which was done by using p53, GFAP and Ki 67 was shown that tissue damage was higher in cisplatin group than cisplatin+ edaravone group and this difference was found to be statistically significant (p< 0.05). Conclusion: The findings of our study suggest that edaravone therapy may be effective in the prevention and treatment of cisplatin-induced brain injury.